Analysis of a cross between green and red fluorescent trypanosomes. (21st July 2006) - Gibson, W.; Peacock, L.; Ferris, V.; Williams, K.; Bailey, M.
Abstract : Trypanosoma brucei undergoes genetic exchange in its insect vector, but the mechanism is unknown and no one has yet seen the process. By crossing genetically engineered red and green fluorescent trypanosomes, we have been able to pinpoint the location of genetic exchange in the fly and search for intermediate stages. In experimental crosses of red and green parental trypanosomes, yellow hybrid trypanosomes first appeared in the fly salivary glands as early as 13 days after infection and were observed only in flies with a mixture of red and green trypanosomes in one or both salivary glands. Despite high numbers of flies with mixed infections, yellow trypanosomes were not detected in the fly midgut or proventriculus. The hybrid nature of yellow trypanosomes was confirmed by analysis of molecular karyotypes and microsatellite alleles. As well as yellow hybrids, hybrid trypanosomes with red, green or no fluorescence were also recovered from fly salivary glands. Analysis of microsatellite alleles in parental and progeny clones showed Mendelian inheritance. Our findings are consistent with the hypothesis that mating takes place between trypanosomes in the salivary glands of the fly before they attach to the salivary gland epithelium.